Violência no sertão da ressaca a negação dos direitos da população infanto-juvenil em Vitória da Conquista, Bahia (1997-2005) - Santos, João Diogenes Ferreira dos (2007)
The aim of this thesis is to reflect on the social inequality and violence against children and youth, in Vitória da Conquista, between 1997 and 2005. We selected for the study a group of children, under social and personal risk, exploited by prostitution and drugs traffic. On one hand, through the study, we tried to comprehend the complex interrelations between the State, classes and social groups, which take into account a historical and social course marked by violence practices that find a comfortable environment upon the modern Bahian coronelism . On the other hand, we address the analysis of the consequences of the economy reforms of the neo-liberal agenda, which have been recently unfolded into the adoption of local social programs and policies that are characterized as locally focused, fragmentary and related with social protectionism. In order to fulfill this task, we ground the research on the particular social and political constitution of the district, whose government has been led by Labors Party (PT) over twelve years. Within a landscape of widening and increasing political indifference due to the replacement of programs to the universe of the poverty management , to the suppression of rights and the degradation of public spaces, we attempt to reflect through this thesis on its effects on those who live upon the edge of surviving which Giorgio Agamben refers as naked life